Application of the Gait Kinematics Index in Patients with Cerebral Palsy - Katarzyna Jochymczyk-Woźniak; Karolina Wawak; Robert Michnik; Katarzyna Nowakowska-Lipiec (Applied Sciences)
Due to the complexity of the medical issues connected with cerebral palsy (CP), the classification of gait pathologies seems rather difficult. The aim of this study was to asses the usefulness of the Gait Kinematics Index (GKI) from a clinical point of view in the population of patients with CP. The assessment of the possibilities of using the GKI in a group of patients with CP was conducted on the basis of the correlation of its results with the Gillette Gait Index (GGI) and Gait Deviation Index (GDI) values. The distribution of the index values was also evaluated with attention paid to the CP types and treatment methods. Analyses were performed on the basis of the gait test results in a group of 56 healthy children and 72 patients with CP. The GKI values for patients with CP were 1.55 ± 0.66, as opposed to 0.77 ± 0.17 for the reference group. A strong linear correlation was found between the values of the GKI and GGI (r = 0.8 ÷ 0.85), as well as between the GKI and GDI (r = −0.89 ÷ 0.9), obtained in children with CP. In addition, significant differences were found between the results obtained in all the groups of children with CP divided by treatment method (rehabilitation, botulinum, rhizotomy, p < 0.05), whereas in the groups of children divided by CP type, significant differences (p < 0.05) were found solely between diplegia and hemiplegia and between hemiplegia and quadriplegia. The results obtained were the same in the case of the GKI, GGI and GDI. To conclude, the results presented in this work confirm the clinical utility of the GKI in the population of patients with CP.